Defect Analysis of R8 Cover Products Using the Six Sigma Method at PT Amtek Engineering - Rumiris Lestari Rita Silalahi; Hery Irwan (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
Quality consistency is a critical requirement in automotive component manufacturing, particularly in precision stamping processes where visual conformity, product identification, and physical integrity directly influence customer acceptance. This study investigates quality defects in R8 Cover production at PT Amtek Engineering using the Six Sigma DMAIC (Define–Measure–Analyze–Improve–Control) framework. A descriptive quantitative and observational approach was employed using production and reject records collected from 5–17 May 2024. The Define phase utilized SIPOC and Critical-to-Quality (CTQ) mapping to identify key quality characteristics. Process capability was evaluated through Defect per Unit (DPU), Defect per Opportunity (DPO), Defect per Million Opportunities (DPMO), process yield, and sigma level measurements. Pareto analysis and fishbone diagrams were applied to determine dominant defect categories and their potential root causes. The results indicate that 82,843 units were produced with 4,533 rejected units, resulting in a DPU of 0.0547, a DPO of 0.0109, a DPMO of approximately 10,900, a process yield of 98.91%, and a sigma level of 3.8. Missing and damaged identification was identified as the most significant defect, contributing 33% of total defects, followed by missing lettering at 23%. Root-cause analysis revealed that defect occurrence was associated with operator practices, machine and tooling conditions, inspection procedures, material conformity, and workplace environment. The study proposes improvement actions focused on setup verification, preventive maintenance, tooling management, inspection standardization, operator competency development, and incoming material control. These findings provide an empirical basis for enhancing process capability and strengthening quality assurance in precision stamping operations.